ТАШКЕНТСКИЙ ГОСУДАРСТВЕННЫЙ СТОМАТОЛОГИЧЕСКИЙ ИНСТИТУТ 3D ПЕЧАТЬ В СОВРЕМЕННОЙ СТОМАТОЛОГИИ - Манукян, А.О.; Амануллаев, Р.А. (Educational Research in Universal Sciences, 2023)
3D printing has been hailed as a disruptive technology which will change manufacturing. Used in aerospace, defence, art and design, 3D printing is becoming a subject of great interest in surgery. The technology has a particular resonance with dentistry, and with advances in 3D imaging and modelling technologies such as cone beam computed tomography and intraoral scanning, and with the relatively long history of the use of CAD CAM technologies in dentistry, it will become of increasing importance. Uses of 3D printing include the production of drill guides for dental implants, the production of physical models for prosthodontics, orthodontics and surgery, the manufacture of dental, craniomaxillofacial and orthopaedic implants, and the fabrication of copings and frameworks for implant and dental restorations. This paper reviews the types of 3D printing technologies available and their various applications in dentistry and in maxillofacial surgery.